Complain Responses Used By Javanese Learners Of English - Nidyawati, Andriyani, Agus Wijayanto, Ph.D, Siti Zurhriah Ariatmi, M. Hum (2014)
This study focuses on the type of complaint responses strategy using the theory of pragmatic strategy by Razekh and politeness strategy by Brown and Levinson. This study aim at (1) describing the complaint responses are used by Javanese learners of English, (2) explaining the differences in complaint responses given by male and female EFL students, (3) explaining the politeness strategies which are involved in complain responses used by Javanese learners of English. This research applies descriptive qualitative metho. The data are the utterances of the forty Javanese students of Department English Education at seventh semester at Muhammadiyah University of Surakarta. The way to collect data is using a questionnaire by giving DCT. The subject consists of twenty male and twenty female participants. The data of complaint responses were analyzed by the coding schema in Eslami and Rasekh (2004) also added by Brown and Levinson (1987) theory as the type of politeness strategy. The result shows that complaint responses based on the coding schema in Eslami &Rasekh (2004) are various. Both, in direct complaint and indirect complaint, IFIDs was as the most appeared strategy used by EFL students, although there were some strategies also used by the participants, for example emotional exclamations, acceptance of responsibility. The different gender influences the complaint responses. In this case, IFIDs has the highest frequency used by both male and female participants in all DCT. However, male used is more frequently than female. As for politeness, positive politeness (PP) was the most appeared strategy which was used by male and female students in almost every situation given, while the subtype of PP mostly used was PP 13 (give or ask reason). Then, negative politeness (NP) was more frequently used by the participants than bald on record. Finally, off record is the least politeness strategy used by the participants. But, the data showed that not all the complaint responses by the participants involved in politeness strategy.